An unusual cause of pancytopenia: Whipple's disease - Nay T. Tun; Shwetanshu Shukla; Jaykrishnan Krishnakurup; Binu Pappachen; Mahesh Krishnamurthy; Hayman Salib (Greater Baltimore Medical Center, 2014)
Whipple's disease is a systemic infectious disease caused by the bacteria Tropheryma whipplei. The most common clinical manifestations of Whipple's disease are weight loss (92%), hypoalbuminemia and steatorrhea (91%, respectively), diarrhea (72%), arthralgia (67%), and abdominal pain (55%). Neurological signs and symptoms from dementia to oculomasticatory myorhythmia or oculofacioskeletal myorhythmia (pathognomonic of Whipple's disease), lymphadenopathy, and fatigue can also be present. Pancytopenia is a rare and less recognized clinical feature in Whipple's disease patients. We are describing a case where a middle-aged Caucasian male diagnosed with Whipple's disease was found to have pancytopenia. Etiology of pancytopenia is postulated to be due to the invasion of bone marrow by T. whipplei. It is important to recognize that bone marrow involvement by the Whipple bacillus is not uncommon. In the presence of lymphadenopathy and pancytopenia, clinicians should think of Whipple's disease as a differential diagnosis apart from lymphoma or other non-specific granulomatous reticuloendothelial disorders.